(untitled) (Revista de Ciências Agroveterinárias, 2017)
The objective was to evaluate the effect of supplementation with calcium soaps of fatty acids (SCAF) in the productive and reproductive performance of animals kept at pasture. The experiment was conducted in sheep breeding sector of IF Goiano – Campus Ceres (GO). After synchronization of estrus and coverage, 32 Santa Ines sheep were randomly chosen by birth order and according with the body condition score (BCS) in four treatments: (TEST - without concentrate supplementation; SUPL - concentrated supplement without including SCAF; GORD5 - concentrated supplement with including 5.0% of SCAF and; GORD10 - concentrated supplement with the inclusion of 10.0% SCAF). The arrays were kept in Tanzania pasture (Panicum maximum) and supplementation began on the first day postpartum and was maintained through 60 days postpartum (dpp). They assessed the body weight (BW) and BCS of all sheep every 15 days. After 60 days trial the percentage of sheep who have expressed estrus and first estrus birth interval (IBFE) of matrices were evaluated. The other phase of the study consisted of the evaluation of the medium daily gain (MDG) and BW of lambs from birth to 60 days old. There was no effect of supplementation with or without SCAF (p>0.05) on the BW, BCS sheep and BW and MDG of lambs. The percentage of estrus was not influenced by experimental diets. The supplementation concentrate without inclusion of SCAF to 60 dpp reduces IBFE, while the inclusion of SCAF does not promote improvement in the productive and reproductive performance of Santa Ines grazing managed sheep.